2018
DOI: 10.1038/s41598-018-36324-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and correlation between phylogeny and functional traits of cowpea (Vigna unguiculata L. Walp.)-nodulating microsymbionts from Ghana and South Africa

Abstract: Cowpea (Vigna unguiculata L. Walp.) is indigenous to Africa, and highly valued for its N2-fixing trait and the nutritional attributes of its grain and leaves. The species’ ability to establish effective symbiosis with diverse rhizobial populations gives it survival and growth advantage in N-limited environments. To explore the functional diversity and phylogenetic positions of rhizobia nodulating cowpea in Africa, nodules were collected from various cowpea varieties grown in soils from the Guinea savanna and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 48 publications
13
31
0
Order By: Relevance
“…The use of this strategy fits to the selection of bacterial isolates for biotechnological applications as inoculants, due to the increasing of the selection of putative rhizobial over the non-rhizobial strains. In our collection, we obtained a total of 64% of all slow growing isolates as positive for nodC amplification, with 161 positive isolates, in agreement to the isolation of non-rhizobial isolate from nodules in the Brazilian semiarid region (Nunes et al 2018) and in African continent (Mohammed et al 2018).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The use of this strategy fits to the selection of bacterial isolates for biotechnological applications as inoculants, due to the increasing of the selection of putative rhizobial over the non-rhizobial strains. In our collection, we obtained a total of 64% of all slow growing isolates as positive for nodC amplification, with 161 positive isolates, in agreement to the isolation of non-rhizobial isolate from nodules in the Brazilian semiarid region (Nunes et al 2018) and in African continent (Mohammed et al 2018).…”
Section: Discussionsupporting
confidence: 74%
“…For the new isolates, 7 out of 10 were related to B. yuanmingense c o r r o b o r a n t t o t h e h i g h e f f i c i e n c y o f c o w p e a B. yuanmingense-like isolates in Brazil (Rufini et al 2014), especially in Brazilian drylands (Martins et al 2003;Marinho et al 2017). The seven efficient B. yuanmingense-like bacteria were distributed to 6 out of 7 different lands use systems evaluated, confirming the high versatility of the bacteria closest relates do this species and their establishment in different land use systems (Mohammed et al 2018;Ndungu et al 2018;Jaiswal and Dakora 2019) and also their high symbiotic efficiency with cowpea.…”
Section: Discussionmentioning
confidence: 64%
“…Besides soil moisture, Mohammed et al (2018) also reported recently that soil mineral nutrients can influence the distribution of bradyrhizobia nodulating cowpea in the soils of South Africa and Ghana. Here, the South African bacterial symbionts were highly influenced by the endogenous soil concentrations of N, P, and Na, in contrast to Ghana, where B, Mn, and Fe had a major influence in the distribution of soil bradyrhizobia.…”
Section: Factors Influencing Bradyrhizobium Distribution In African Smentioning
confidence: 85%
“…The Guinea savanna and Sudano-Sahelian regions of Ghana, as well as the low veld of South Africa were also explored for the biogeographic distribution of root-nodule bacteria nodulating cowpea in the two countries. In that study, sequence analysis of core genes ( atpD, glnII, gyrB , and rpoB ) and symbiotic genes ( nifH and nodC ) revealed the presence of highly diverse Bradyrhizobium species nodulating cowpea that were closely related to B. daqingense, B. subterraneum, B. yuanmingense, B. embrapense, B. pachyrhizi , and B. elkanii , as well as a number of unidentified novel Bradyrhizobium isolates (Mohammed et al, 2018). Multivariate analysis also showed that the distribution of these Bradyrhizobium species was strongly influenced by the concentration of mineral nutrients in the soils (Mohammed et al, 2018).…”
Section: Diversity Of Microsymbionts Nodulating Indigenous Vigna Specmentioning
confidence: 96%
“…In Africa, the N 2 -fixing ability and diversity of native soil rhizobia nodulating cowpea, groundnut, Bambara groundnut, common bean, soybean, and Kersting's bean have been established (Chibeba et al, 2017;Puozaa et al, 2017Puozaa et al, , 2019Zinga et al, 2017;Chidebe et al, 2018;Gyogluu et al, 2018;Mohammed et al, 2018Mohammed et al, , 2019. However, their N contribution in cropping systems is still not properly understood.…”
Section: Introductionmentioning
confidence: 99%